Scheduling terminology for oral and maxillofacial surgery. Are we speaking a universal language?. Issue 4 (May 2017) - Howe, T.E.; Varley, I.; Allen, J.E.; Glossop, A.; McKechnie, A.
Abstract: Use of a universal vocabulary to assist with the scheduling of operations has been shown to considerably reduce delays and improve the use of theatre resources. Within the UK the National Confidential Enquiry into Patient Outcome and Death (NCEPOD) has established a classification to assist with the triage of both emergency and non-emergency operating lists. We completed a survey to assess the uptake and understanding of this classification when scheduling maxillofacial operations. From a list of eight scheduling terms, respondents had to choose one each for 20 different clinical situations (that represented equally) immediate, urgent, expedited, and elective operations as defined by them. A total of 50 surveys were collated. Only 65% of answers selected represented NCPOD terms. 25% of answers represented a term higher and 18% a term lower, on the scale of intervention for the same category of situation. Current NCEPOD terms do not seem to be used universally and are poorly understood. Considerable variation in terminology exists when scheduling maxillofacial operations.